The First Reported Case of a Child with Two Different Rare Metabolic Disorders: Very Long-Chain Acyl-CoA Dehydrogenase Deficiency and Encephalomyopathic Mitochondrial DNA Depletion Syndrome 13 - Alotaibi, Maha; Alqasmi, Amal; Albassam, Faisal; Alkahtani, Turki; Alqahtany, Muath; Alkhaldi, Mohammed (Global Medical Genetics, 2023)
One of the most common inborn errors in fatty acid β oxidation (FAO) is a very long-chain acyl-coenzyme A dehydrogenase (VLCAD) deficiency. It is autosomal recessive. The enzyme used in the first phase of FAO is VLCAD. The enzyme is responsible for β oxidation spiral pathway's initial step, the dehydrogenation process of long-chain fatty acyl-CoA. The phenotypes include hypoglycemia, hepatomegaly, cardiomyopathy, and occasionally abrupt mortality. Most VLCAD deficiencies in newborns are now detected during the neonatal period due to the development of newborn screening programs. Mitochondrial DNA depletion syndromes (MTDPS) are one of the rarest metabolic disorders. It is an autosomal recessive disease caused by defects in genes necessary for the maintenance of mitochondrial DNA (mtDNA). One of these FBXL4 (F-box and leucine-rich repeat protein 4) variants causes encephalomyopathic mtDNA depletion syndrome 13 (MTDPS13), which presents as a failure to thrive, severe global developmental delay, hypotonia, early infantile onset of encephalopathy, and lactic acidosis. We report here the case of a Saudi infant born to consanguineous parents who presented to us with severe failure to thrive, profound neurodevelopmental delays, and facial dysmorphic features. Whole-exome sequencing (WES) showed the infants had MTDPS13. The FBXL4 variant c.1698A > G p. (Ile566Met) has previously been described as a disease that causes developmental delay and lactic acidosis, and another variant has also been detected in the patient. The ACADVL variant c.134C > A p. (Ser45*) has previously been described to cause VLCAD deficiency. A comprehensive literature review showed our patient to be the first case of MTDPS13 and VLCAD reported to date worldwide.
Keywords: FBXL4; hypoglycemia; mitochondrial DNA; mitochondrial diseases; very long-chain acyl-CoA dehydrogenase deficiency; pediatric genetics